Enriched silvopastoral systems: a proposal for integrating conservation into livestock production in rural communities in Los Tuxtlas, Mexico - de la Peña-Domene, Marinés; Ayestarán-Hernández, Luz María; Márquez-Torres, José Flavio; Martínez-Monroy, Fernando; Rivas-Alonso, Edith; Carrasco-Carballido, Patricia Valentina; Pérez-Cruz, Miguel Neftalí; Chang Landa, Frankis Antonio; Martínez-Garza, Cristina (Instituto de Ecología, A.C., 2022)
Background and Aims: Livestock production is the main cause of habitat destruction and species extinction worldwide. It is also a strong contributor to greenhouse gas emissions. In Latin America, cattle ranching is the main economic activity of many rural communities, so establishing restoration plantations in pastures could provide ecosystem services with direct and indirect benefits for cattle production. Silvopastoral systems reach production levels equal to or higher than conventional systems and prolong the useful life of productive land. This paper examines the integration of silvopastoral systems with restoration with native trees of economic and conservation importance. We refer to these plots as enriched silvopastoral systems (ESPS). We present the results of the first stages of establishment of these systems which seek to improve the livelihoods of ranchers and to maintain landscape connectivity, ecosystem services, and the conservation of tropical forest species.Methods: In 2016, we established ESPS in a pilot plot in Los Tuxtlas, Mexico, planting 16 native tree species and Leucaena esculenta (DC.) Benth. as a fodder tree. At the same time, workshops on livestock alternatives were held in the ejido of Balzapote to increase the possibilities of social incidence.Key results: The survival of the planted trees was on average 40.7%. The demonstration plot has served to bring farmers closer to different more productive alternatives. We observe a reduction in maintenance costs because the producers are not dependent on external supplies.Conclusions: As a result of the implementation of the ESPS, livestock production improved, resulting in a decrease in the use of agrochemicals. ESPS will bring complexity to the landscape resulting in more resilient systems in the face of climate change.